Fabrication of Ni, Cr, W reinforced new high alloyed stainless steels for radiation shielding applications - Aygün, B.; Şakar, E.; Korkut, T.; Sayyed, M. I.; Karabulut, A.; M. Zaid, M. H. (Elsevier, 2019)
Stainless steel is commonly used in radiation applications for its high temperature resistance and fine mechanical properties. In this study, three types of high alloyed stainless-steel samples were produced. Before the production, GEANT4 Monte Carlo simulation toolkit was used to estimate the total fast neutron macroscopic cross sections and gamma mass attenuation coefficients. The hot-pressing process and the powder metallurgy method were applied. We tested samples’ chemical and mechanical strength. Samples were exposed to both gamma rays and fast neutrons. The obtained simulation and experimental results for both neutron and gamma radiation are compatible. According to the simulation and experimental results, neutron shielding capacity of the new stainless-steel alloys is higher than the most commonly used 316LN stainless steel in nuclear applications. Among the prepared samples, SSA1 steel has the smallest half value layer at the all examined energies. All the prepared samples posses higher mass attenuation coefficient values and lower half value layer than 316LN steel. This indicates that the produced three new high alloyed stainless-steel samples have high gamma absorption capacity when compared to 316LN steel.